Radar Detection Simulation by Digital Twins of Target and Antenna System - A. S. Grigoriev; A. A. Kazantsev; A. M. Terentyev; B. S. Stavtsev (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The entire concept of product development is currently undergoing significant changes. The application of digital twin technology allows the focus of development to be shifted to the earliest stages, thereby significantly reducing not only potential risks, but also saving the required time and material resources. Classical statistical approaches to evaluating the detection capabilities of radar systems fail to provide a complete dynamic picture due to the large number of varying parameters.Aim. Development of an algorithmic support for simulating the radar detection process using digital twins of the antenna system and the observation object.Materials and methods. Radar equation multipliers were presented by frequency, angular, polarization dependencies, calculated using their digital models (twins). Numerical electrodynamics methods were used to calculate the directivity characteristics of the antenna element and the backscattering characteristics of the object, implemented in the ANSYS HFSS automated design environment. Mathematical and computer modeling methods were used to coordinate the results of numerical simulations. The MATLAB application package was used to form the directivity characteristics of the antenna array, to obtain the dynamic signal-to-noise ratio, and to analyze the probability of detection.Results. The possibility of using digital twin technology to verify the detection capability for a radar system when observing an object of the specified class is demonstrated. The signal-to-noise dynamic dependence of the given radar system, space object, and observation scenario, presented by their digital models, was calculated. The function of detection probability density was calculated, which demonstrated an insufficient detection capacity of a radar system in the case of observation of such type of objects.Conclusion. The significance of the present study lies in the development of an algorithmic support using digital twin technology. The developed support can be used to estimate the probability of detection of specified objects by a radar system when implementing various technical solutions at early stages of its development.